Neuroparenting dalam Stimulasi Kecerdasan Anak Usia Dini melalui Interaksi Positif di Rumah - Loeyyina Khuru’Aini; Endah Tejaningsih (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2024)
Neuroparenting is a neuroscience-based parenting approach that emphasizes the importance of stimulating children's brain development through warm communication, play, and emotional parental involvement. This study aims to describe the implementation of Neuroparenting in stimulating early childhood intelligence through positive interactions at home. This study used a qualitative approach with a descriptive research type. The subjects were parents of children aged 4–6 years. Data collection techniques were carried out through observation, in-depth interviews, and documentation. Data analysis used the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that the application of Neuroparenting through warm communication, playing together, reading stories, providing positive affirmations, and involving children in daily activities can help the development of language, cognitive, social-emotional, creativity, and self-confidence. Children who receive positive stimulation consistently appear more active in speaking, easily express opinions, and are better able to interact with their surroundings. Based on the results of the study, it can be concluded that Neuroparenting through positive interactions at home is an effective parenting approach in supporting the optimal development of early childhood intelligence.